Autoeficácia e sentidos de escolarização de estudantes com paralisia cerebral no ensino médio - DELFITO, Michelle (2025)
This study is linked to Research Line 2: "Teacher Training and Professional Action and Educational Practices" and the research group "Construction of Subjectivity Processes in the School Context," of the Graduate Program in Education at Unoeste. The inclusion of students with Cerebral Palsy (CP) in high school is a topic of growing relevance, aiming to ensure equal opportunities and access to quality education. This movement seeks not only to promote the full participation of these students in the school environment but also to contribute to a more just and inclusive society, where the individuality and potential of each student are respected and valued. Self-efficacy, a concept introduced by Albert Bandura, is fundamental for academic performance, defined as students' belief in their own abilities to achieve goals and successfully complete tasks. In the high school context, students – especially those with disabilities – face challenges that directly affect their self-efficacy and, consequently, their academic success. This process is particularly significant for students with Cerebral Palsy, who face additional barriers in their educational journey and benefit from strategies that strengthen their self-confidence and coping abilities. This dissertation is structured in a multipaper format, divided into three studies. Study I explores the challenges and perspectives of including these students, emphasizing the need for a personalized approach that addresses individual needs and promotes effective participation in the school environment. The results highlight the importance of tailored strategies to meet students’ individual needs, ensuring their full inclusion and participation in education. Despite advancements, further efforts are required to guarantee effective inclusion in high school. Study II indicates that family support and experiences of success are essential in building young people’s self-efficacy, particularly for students with disabilities. However, gaps persist in the implementation of inclusive educational policies and in teacher training for diverse contexts. Mindfulness programs, for example, have proven effective in promoting self-efficacy, provided they are adapted to the specific needs of each student. The research also underscores the importance of collaborative planning to create school environments that value diversity and foster the holistic development of students. Evidence suggests that inclusive teaching practices, welcoming school environments, and individualized support are crucial for strengthening self-efficacy, thereby improving academic performance and promoting students’ emotional and social well-being. Study III, a case study, reveals that for a specific student, self-efficacy was shaped by factors such as family support, interactions with teachers and peers, and the use of coping strategies. The support network was essential for personal growth and managing limitations related to the disability, highlighting the importance of ensuring access to resources that encourage student autonomy. Facing challenges contributed to the development of skills and strengthened the student’s confidence in her own abilities. In conclusion, the three studies reinforce the urgency of educational policies that prioritize strengthening self-efficacy and promoting effective inclusion in high school. By adapting the school environment to support the development of self-efficacy, a learning space is created that values diversity and prepares all students, with or without disabilities, to face future challenges, fostering truly inclusive education.